2007
DOI: 10.1007/s00264-007-0480-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological approach to treatment of intra-articular proximal tibial fractures with double osteosynthesis

Abstract: The treatment of intra-articular proximal tibial fractures is associated with complications, and much conflicting literature exists concerning the treatment of choice. In our study, an attempt has been made to develop an ideal and adequate treatment protocol for these intraarticular fractures. The principle of double osteosynthesis, i.e., lateral minimally invasive plate osteosynthesis (MIPO), was combined with a medial external fixator to treat 22 intra-articular proximal tibial fractures with soft tissue inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…[13][14][15] The use of a raft construct through a locking plate provides adequate stability to the subchondral bone without filling the metaphyseal void with a bone graft or bone substitute, and achieves radiological union after a mean of 8 (6)(7)(8)(9)(10)(11)(12)(13)(14) weeks, which is similar to other techniques with bone grafting. 16,17 Complications after bone grafting have been reported. In patients with iliac crest bone grafting, up to 3% developed infection necessitating readmission, up to 22% developed minor complications such as persistant discomfort, cutaneous nerve damage, local wound complications (superficial wound infection, seroma, and haematoma), and up to 38% had pain after 6 months and in some cases beyond 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The use of a raft construct through a locking plate provides adequate stability to the subchondral bone without filling the metaphyseal void with a bone graft or bone substitute, and achieves radiological union after a mean of 8 (6)(7)(8)(9)(10)(11)(12)(13)(14) weeks, which is similar to other techniques with bone grafting. 16,17 Complications after bone grafting have been reported. In patients with iliac crest bone grafting, up to 3% developed infection necessitating readmission, up to 22% developed minor complications such as persistant discomfort, cutaneous nerve damage, local wound complications (superficial wound infection, seroma, and haematoma), and up to 38% had pain after 6 months and in some cases beyond 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous series of proximal tibia fractures treated with locking plates have shown good results with low complication rates [14]. Table 4 summarises some of the published series of patients with proximal tibia fracture treated with the locking-plate technology as well as the reported major complications.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported 3 deep infections in their comparative retrospective study of 79 patients [35]. Singh et al reported no wound dehiscence or infection in 22 patients with high energy tibial plateau fractures managed with lateral minimally invasive plate osteosynthesis and a medial external fixator [36]. Despite using staged management with a temporary ex fix in high risk patients, there were 3 cases of superficial and one case of deep infection in this series of patients.…”
Section: Discussionmentioning
confidence: 90%